ANALISIS PENGARUH PRODUKTIVITAS TENAGA KERJA, UPAH RIIL, DAN PERTUMBUHAN EKONOMI TERHADAP PENYERAPAN TENAGA KERJA DI 35 KABUPATEN/KOTA JAWA TENGAH - Yossia Tambunsaribu, Romas; Mudakir, Bagio (Diponegoro Journal of Economics, 2013)
The highest level of unemployment in Central Java indicates that the process of employment in 35 district/cities Central Java is still low. Although the economic growths 35 districts/cities in Central Java have been increased, it not be able to absorb the numbers of labor forces. The purpose of this research was to determine the effect of labor productivity, real wages and economic growth on the labor market in Central Java. This study used secondary data analysis tools with the data panel Fixed Effect Model (FEM) approachment or the Least Square Dummy Variable (lSDV) model, which consists of times series data during the period of 2008-2010 and cross section data of 35 districts / cities in Central Java. Result of this study proved that labor productivity gave significant negative effects on employment absorption, while real wages and economic growth have a positive effect on employment absorption. The negative outcome of regression coefficient showed that the increasing number in labor productivity could reduce the amount of employment absorption and the positive regression coefficient indicates that real wages and increasing economic growth could cause to increased employment absorption.Â Â